Analisis Keberhasilan Sistem Informasi Manajemen Menggunakan Model Delone dan Mclean - Herlina, Herlina; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the ways in which user satisfaction and the overall advantages of an information system's implementation are influenced by system, information, and service quality. A thorough statistical study was carried out, which included path analysis for hypothesis testing, Cronbach's Alpha for reliability measurement, factor loading in structural equation modeling (SEM) for validity assessment, and the Kolmogorov-Smirnov test for normalcy. The results show that user happiness is greatly increased by system, information, and service quality, which in turn raises the net benefits. These results align with previous studies, emphasizing that improving these key factors can strengthen organizational efficiency. Additionally, the validity and reliability tests confirm that the research instrument meets the necessary standards. Path analysis further reveals strong correlations between independent and dependent variables, underscoring the importance of high-quality system implementation for maximizing outcomes.